Análise de estabilidade de sistemas aeroelásticos empregando elementos finitos estocásticos e o Método Doublet Lattice - Delgado Filho, Marcelo Araújo (2021)
Flutter is a critical aeroelastic instability, whose consideration is fundamental during the design of any aircraft. Although there are well-established methodologies in the open literature for dealing with the flutter phenomenon, in practice, aeroelastic systems are frequently subjected to parameters variations that, even though vary little, may influence its aeroelastic response considerably. Thus, to make the flutter prediction more realistic and reliably, it is necessary to propose methodologies for dealing with the uncertain parameters. Therefore, this work aimed to evaluate the effect of geometric uncertainty of a wing on its structural and aeroelastic behavior. In this contribution, the wing is modelled as a thin plate by using the so-called stochastic finite element method, in which the spatial variation of the thickness is modelled through the Karhunen-Loève expansion and the uncertainties are introduced on the model by the Monte Carlo simulation. In turn, the non-stationary aerodynamic loads are given according to the doublet lattice method. Then, from the equation of motion of the stochastic aeroelastic system, it was possible to formulate an eigenvalue problem to be solved in order to predict the flutter boundary. The results demonstrated the applicability of the proposed methodology for dealing with parametric uncertainties on aeroelastic systems and their degree of influence on the flutter boundary. It is evident the importance of considering them on aeroelastic systems for dealing with more realistic situations.